2nd International Conference on Creative Multimedia 2022 (ICCM 2022) 2022
DOI: 10.2991/978-2-494069-57-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Melaka Sultanate Tradition in Early Colonial Melaka Municipality

Abstract: The rise of Melaka Sultanate city as the international trade centre and 'emporium of the east' in the fifteenth and early sixteenth centuries has been well explained and discussed by many scholars. The Melaka Sultanate city has gone through two and a half centuries of its historical narrative. However, less academic study has been done to trace the Melaka Sultanate physical constructs and municipality in their geo-location. This study investigates historical records in its attempt to trace Melaka Sultanate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…This approach aimed to identify any remnants of Melaka Sultanate structures, essentially using them as markers. Over the course of the research, the study identified a sequence and alignment of significant locations, such as the primary street passing through Bendahara village, the Sultanate bridge, and the Sultanate gate, based on historical texts [13] & [14]. In the second phase of the study, the focus shifted to creating an inventory with critical annotations.…”
Section: Table 1 a Simplified Framework Of Visual Anthropological Ana...mentioning
confidence: 99%
“…This approach aimed to identify any remnants of Melaka Sultanate structures, essentially using them as markers. Over the course of the research, the study identified a sequence and alignment of significant locations, such as the primary street passing through Bendahara village, the Sultanate bridge, and the Sultanate gate, based on historical texts [13] & [14]. In the second phase of the study, the focus shifted to creating an inventory with critical annotations.…”
Section: Table 1 a Simplified Framework Of Visual Anthropological Ana...mentioning
confidence: 99%
“…It is important to note that the Indian, Chinese and Javanese territories 1613 (which surround the Malay trading territory) were untouched during the 1511 war as they cooperated with Portuguese administration [14]. Therefore, the 3 cornered streets remain as the municipal grid in the tradition of the Melaka Sultanate era [10].…”
Section: Findings From Visual Anthropological Analysismentioning
confidence: 99%